The Association Between Perceptions of Neighborhood Conditions and the Employment of Emerging Adults Formerly Involved in the Juvenile Justice System. Issue 7 (October 2022) - Lee, Lewis H.; Kim, Minseop; Carlson, Catherine; Ellis, Taylor; Johnson, Karen; Pretz, Angela
Although prior research finds that poor neighborhood conditions are negatively associated with employment, little study has focused on emerging adults who formerly had contact with the juvenile justice system and are frequently engaged in informal job markets. Using a hybrid model and three waves from panel data with formerly juvenile justice-involved emerging adults (18–24 at T 1, 20–25 at T 2, 20–26 at T 3 ) collected in Philadelphia and Phoenix ( N  = 947), we find an inter-individual increase in the degree of disorder within the neighborhood decreases weeks worked for community jobs (between-effect), whereas an intra-individual increase in neighborhood condition scores increases weeks worked for under-the-table jobs among emerging adults (within-effect). Some time-variant and invariant sociodemographic factors, including perceived opportunity for work, mental health, substance use, gang membership, race, and education, are significantly related to employment. Our findings reiterate justice-involved young people may have difficulty sustaining formal employment partially due to neighborhood conditions.